2017
DOI: 10.1111/opn.12154
|View full text |Cite
|
Sign up to set email alerts
|

Associations between nursing home performance and hospital 30‐day readmissions for acute myocardial infarction, heart failure and pneumonia at the healthcare community level in the United States

Abstract: Coordinated care between hospitals and nursing homes is essential to reduce readmissions. Nursing homes can improve performance and reduce readmissions by increasing registered nursing homes. Further, communities can work together to create cross-continuum care teams comprised of hospitals, nursing homes, patients and their families, and other community-based service providers to reduce unplanned readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 25 publications
(60 reference statements)
0
22
0
Order By: Relevance
“…However, individuals with worse physical function, hence possibly more frail, are generally more likely to be discharged to a nursing home, and living at a nursing home may alter the risk for readmission in both directions compared to living in ordinary home depending on nursing-home performance, as pointed out in previous studies [38]. Differences in skill and competence levels between nursing homes have also been shown to have an impact [43]. It is worth noting the competing risk due to death; the mortality rates in the more frail and less independent individuals living in nursing homes are higher [38].…”
Section: Plos Onementioning
confidence: 85%
“…However, individuals with worse physical function, hence possibly more frail, are generally more likely to be discharged to a nursing home, and living at a nursing home may alter the risk for readmission in both directions compared to living in ordinary home depending on nursing-home performance, as pointed out in previous studies [38]. Differences in skill and competence levels between nursing homes have also been shown to have an impact [43]. It is worth noting the competing risk due to death; the mortality rates in the more frail and less independent individuals living in nursing homes are higher [38].…”
Section: Plos Onementioning
confidence: 85%
“…It is consistent with data from the Behavioral Risk Factor Surveillance System (BRFSS) studies that showed higher prevalence of MI at ages younger than 65 in the lagging states ( 31 ) potentially associated with higher prevalence of MI risk factors in the lagging states among younger adults ( 24 – 27 , 32 ). Finally, observed lower survival rates after MI diagnosis and lower remaining LE at age 65 among MI patients may be explained by earlier MI onset ( 31 ), lower rate of cardiac rehabilitation ( 33 ), worse nursing home performance ( 34 ), lower adherence to medication intake for arterial hypertension and cholesterol-lowering ( 35 ), and longer pre-hospital time to the percutaneous coronary intervention (PCI) centers ( 36 ) in the lagging states.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the research have separated the three entities, and examined them at each level of the healthcare service 20–23. For example, factors affecting hospital readmissions have been explored within the realm of primary healthcare services (eg, nurse turnover, nurse staffing and performance and care quality)24–26 or secondary healthcare services (eg, staff responsiveness, length of stay and medication-related events) 27–29…”
Section: Introductionmentioning
confidence: 99%